THE IDENTITY OF USTILAGO AMADELPHA VAR. GLABRIUSCULA - MIEN A. RIFAI (BRIN Publishing (Penerbit BRIN), 1980)
The host of this smut variety is identified as Panicum repens L. The fungus is considered conspecific with Ustilago overeemii Cif., which sub- sequently is reclassified as Sporisorium overeemii (Cif.) Rifai, comb. nov.